Peran Brand Image dalam Memediasi Pengaruh Digital Marketing, dan Product Quality terhadap Purchse Decision: Studi Produk Make Over di E- Commerce Shopee Kota Malang - Najatul Muti, Tria; Firmansyah, Fani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
In the current digital era, technological advancements significantly influence consumer behavior, particularly through e-commerce platforms like Shopee. This study aims to analyze the impact of digital marketing and product quality on purchase decisions, with brand image serving as a mediating variable. Using a quantitative approach, data were collected via online questionnaires from 125 respondents who were Make Over consumers in Malang City. SmartPLS software was employed for data analysis. Results show that both digital marketing and product quality significantly influence purchase decisions directly and indirectly through brand image. These findings underscore the importance of optimizing digital strategies and maintaining product quality to enhance brand perception and consumer purchase decisions.